2016
DOI: 10.3892/etm.2016.3642
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin inhibits inflammation and chondrocyte apoptosis by regulation of the PI3K/Akt signaling pathway in a rat model of osteoarthritis

Abstract: Shikonin has previously been shown to have antitumor, anti-inflammatory, antiviral and extensive pharmacological effects. The aim of the present study was to explore whether the protective effect of shikonin is mediated via the inhibition of inflammation and chondrocyte apoptosis, and to elucidate the potential molecular mechanisms in a rat model of osteoarthritis. A model of osteoarthritis was established in healthy male Sprague-Dawley rats and 10 mg/kg/day shikonin was administered intraperitoneally for 4 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…1 The pathological process of OA mainly involves the degeneration of cartilage tissue and the loss of joint function; joint pain and swelling are the main clinical symptoms, and it will develop into movement difficulties caused by limb stiffness, which seriously affects the life quality of patients. 2,3 At present, the pathogenesis underlying OA is still unclear, the clinical treatment of OA is limited to the remission of OA symptoms, and no independent formulations can affect the pathogenesis of OA. 4 Therefore, it is critical to explore the possible pathogenesis of OA and nd effective therapeutic agents for the prevention and treatment of OA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The pathological process of OA mainly involves the degeneration of cartilage tissue and the loss of joint function; joint pain and swelling are the main clinical symptoms, and it will develop into movement difficulties caused by limb stiffness, which seriously affects the life quality of patients. 2,3 At present, the pathogenesis underlying OA is still unclear, the clinical treatment of OA is limited to the remission of OA symptoms, and no independent formulations can affect the pathogenesis of OA. 4 Therefore, it is critical to explore the possible pathogenesis of OA and nd effective therapeutic agents for the prevention and treatment of OA.…”
Section: Introductionmentioning
confidence: 99%
“…18 Studies have also reported that PI3K/Akt signaling pathway is one of the pathways affected the degradation of cartilage matrix OA and apoptosis of cartilage cells by inhibiting the activation of its downstream protein NF-KB and thereby inhibiting the expression of MMPs. 3,19,20 However, whether Sal B inhibits the inammatory response and apoptosis of OA induced by IL-1b via PI3K/Akt pathway has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K-Akt, Notch, Wnt and MAPK signaling pathways are well known to be involved in OA pathogenesis, and regulate a variety of biological processes, including inflammation, cell growth, survival and metabolism [17][18][19]. For examples, activation of the PI3K-AKT pathway in chondrocytes accelerates cartilage degradation, while inhibition of the PI3K-AKT pathway attenuates cartilage degradation and inflammatory responses [20,21]. Notch pathway plays a critical role in cell fate via regulating differentiation and apoptosis [22], and is activated in OA [23].…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the protective mechanism of shikonin in SCI rats, the expression levels of HMGB1, TLR4 and NF-κB were determined and the results showed that the improved tissue repair and decreased inflammation induced by shikonin might be involved in the down-regulation of HMGB1/TLR4/NF-κB signaling pathway. Previous publication revealed that shikonin could inhibit inflammation and apoptosis through PI3K/ Akt signaling pathway in a osteoarthritis rat model [32]. Latest report indicated that shikonin attenuated cell apoptosis in ConA-induced hepatitis through up-regulating expression of Bcl-2 and reducing expression of Bax, caspase 9 and p-JNK [33].…”
Section: Discussionmentioning
confidence: 99%